1999
DOI: 10.1038/sj.bjc.6690457
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, double-blind, placebo-controlled randomized trial of cimetidine in gastric cancer

Abstract: Summary Cimetidine is thought to inhibit suppressor T-lymphocyte function and preliminary evidence from a randomized trial indicated that it might prolong survival for patients with operable and inoperable gastric cancer. The British Stomach Cancer Group conducted a randomized, double-blind, placebo-controlled trial examining the effects of cimetidine (400 mg or 800 mg twice a day) on the survival of patients with early (stages I, II and III: n = 229) and advanced (stages IVa and IVb: n = 201) gastric cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…3), and noted that the perioperative use of cimetidine in gastric cancer patients could help restore diminished cellular immunity. Milito and Fais [43], Dillman et al [44], and Jiang et al [45] were in agreement with this opinion, but Langman et al [46] reported that cimetidine did not show significantly more influence on the survival of patients with gastric cancer than placebo. Therefore, further investigation is required into the effects of cimetidine.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 66%
“…3), and noted that the perioperative use of cimetidine in gastric cancer patients could help restore diminished cellular immunity. Milito and Fais [43], Dillman et al [44], and Jiang et al [45] were in agreement with this opinion, but Langman et al [46] reported that cimetidine did not show significantly more influence on the survival of patients with gastric cancer than placebo. Therefore, further investigation is required into the effects of cimetidine.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 66%
“…In another report, pre-operative cimetidine led to significant lymphocytic infiltration in colorectal tumors [21]. However, three recent randomized trials in gastric cancer and one large randomized Danish study in colorectal cancer patients, who received ranitidine post-operatively, showed no overall survival benefit [22][23][24][25]. A subgroup analysis in the Danish study showed a survival benefit for patients who received ranitidine but did not receive blood transfusions nor developed post-operative infectious complications [26].…”
Section: Introductionmentioning
confidence: 95%
“…In 1988 it was reported that post-operative treatment with cimetidine improved survival of patients with any stage of gastric cancer (10). But, in a more recent and larger study organized by the British Stomach Cancer Group, cimetidine had no effect on survival when compared to the placebo group (11). Recently, Kobayashi et al (12) showed that cimetidine could block the adhesion of a colorectal tumor cell line to endothelial cells in vitro and could suppress the formation of hepatic metastasis in a nude mouse model via the down-regulation of the cell surface expression of the adhesion molecule E-selectin on endothelial cells.…”
Section: Cimetidine Inhibits the Adhesion Of Gastric Cancer Cells Expmentioning
confidence: 99%